Quality Characteristics of Jack Bean (Canavalia ensiformis L.) Tempeh Milk with Addition of Ajwa Date (Phoenix dactylifera L.) and Various Types of Stabilizers - Giovani, Sarah; Putri, Afiya Deliana; Adelina, Nadya Mara; Setiyoko, Agus (Journal of Agri-Food Science and Technology, 2024)
Jack bean tempeh was processed into jack bean tempeh milk. The addition of Ajwa date can improve the organoleptic and nutritional value of jack bean tempeh milk. Moreover, stabilizers must be added while making jack bean tempeh milk to enhance its quality. This study contributed to determining the effect of various stabilizers on jack bean tempeh milk quality. The treatments were (F1) the addition of iota carrageenan stabilizer (0.1%), (F2) the addition of gum Arabic stabilizer (0.1%), (F3) the addition of pectin stabilizer (0.1%), and (F4) the addition of carboxy methyl cellulose (CMC) stabilizer (0.1%). The results of this study showed that the stabilizer types had no significant effect on the organoleptic color, texture, and taste of the jack bean tempeh milk. The selected formulation was based on the hedonic quality test in the parameters of color and aroma, namely formula F4, which was jack bean tempeh milk with the addition of a CMC stabilizer. The results of the chemical characteristics of F4 jack bean tempeh milk was protein content of 0.65%, fat content of 2.48%, and antioxidant activity (IC50) of 7760 ppm. The physical characteristics of F4 jack bean tempeh milk was a pH value of 5.8, total dissolved solids of 20.7°Brix, a viscosity of 13.43 cP, L* value of 60.61, a* value of -0.12, and b* value of 19.56.